Development Of Interterritorial Cooperation Between Uzbekistan And Russia (Texas Journal of Multidisciplinary Studies, 2022)
This article highlights the historical and modern features of Russia-Uzbekistan relations, interregional relations and historical aspects of socio-political, economic and cultural relations.